A hybrid metaheuristic model for job shop rescheduling problem - Mohamed Din, Aniza; Ku-Mahamud, Ku Ruhana; Yusof, Yuhanis; Mahmuddin, Massudi (2012)
This paper discusses on developing a hybrid metaheuristic model to tackle the problem of changing environment in the job shop scheduling problem.The main idea is to use the model to develop building blocks of partial schedules that can be used to provide backup solutions when disturbances occur during production.Each partial schedule is assigned a fitness value for the selection of final population of best partial schedules.The results of the experiments show an improvement from a previous work. Future work on this study is also discussed.